An interactive teaching/learning approach to the design of robust linear control systems using the closed-loop shaping methodology. Issue 2 (2020) - Díaz, José Manuel; Dormido, Sebastián; Costa-Castelló, Ramon
Abstract: Usually the controller is designed working on the open-loop transfer function. However, it is also possible to design the controller working on the closed-loop transfer functions. The closed-loop shaping methodology offers a straightforward framework which allows designers and students to focus on the required specification fulfillment and dealing with inherent linear systems limitations without complex computations or using difficult algorithms. This article summarizes the basic ideas of the manual closed-loop shaping methodology, and its application to the design of robust controllers for uncertainty linear systems. An interactive software tool for learning/teaching this methodology is also presented.